It is not only about the depth of processing: What if eye am not interested in the text?. (December 2018) - Catrysse, Leen; Gijbels, David; Donche, Vincent
Abstract: This study aims at extending current research on how the interaction between cognitive processing and topic interest shapes the online learning process of students when learning from expository texts. We used eye tracking to monitor the reading and learning behaviour of 31 students in higher education. In addition, we used self-report questionnaires to map students' general disposition towards deep and surface processing and their topic interest. Cued retrospective think-alouds were conducted to capture students' levels of processing during learning from text. We examined the interaction between levels of processing and topic interest on eye movement measures. Results indicate that high-interested students who use more deep processing reread key sentences longer than detailed sentences and thus process these sentences more deeply. This study advances present knowledge in the field by focusing on the online learning process and stresses the importance of giving students learning contents that spark their interest. Highlights: Students using more deep levels of processing do not reread key sentences longer than details. Highly interested students using more deep levels of processing reread key sentences longer than details. There is an important interplay between topic interest and deep processing during the online learning process.